DETERMINANT TRUE DISCOUNT PADA PENAWARAN SAHAM PERDANA PERIODE 2010-2014 - Pratiwi, Puput Ragil; Sulistiyani, Tina (Jurnal Fokus Manajemen Bisnis, 2017)
This study aims to obtain empirical evidence regarding DETERMINANT TRUE DISCOUNT IN PRESIDENT STOCK OFFERS 2010-2014. Diamana, Underpricing is proxied by True discount as the dependent variable and the Underwriter Reputation, Company Size, Company Age, Type of Company or Industry Sector, and Share Percentage offered as independent variables. The population in this study are all companies that made an initial public offering on the Indonesia Stock Exchange in 2010 to 2014 as many as 126 companies. The sample of this research were 80 companies taken from the population using purposive sampling method, besides that the researchers used secondary data type data. The results of this study indicate that the variable Company Size, Company Type or Industrial Sector, and the percentage of shares offered affect the True Discount given to investors in companies that register (register) on the Indonesia Stock Exchange in 2010-2014. While the Underwriter Reputation and Company Age variables do not affect the True Discount given to investors in companies that register (register) on the Indonesia Stock Exchange in 2010-2014. Then Reputation Underwriter (RU), Company Size (size), Age of Company (Maturity), Type of Company (JP), Percentage of Shares offered (PS) jointly affect the True Discount given to investors in companies that register (listing ) on the Indonesia Stock Exchange in 2010-2014.